Использование теплостоков для стимулирования гетерогенного зародышеобразования - Серга, М.А.; Коваленко, Т.В.; Шевчук, С.Н.; Лысаковский, В.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The opportunity of use heat sink for creation melt supersaturation, which is necessary for stimulation heterogeneous nucleation is shown, that allows to provide formation and growth of diamond single crystals in the required points of a substrate.